Pengembangan kapasitas SDM aparatur dalam penyelenggraan pemerintahan desa di Desa Kenongo Kecamatan Tulangan Kabupaten Sidoarjo - Isnaini Rodiyah; Hendra Sukmana; Ilmi Usrotin Choiriyah (Publisia: Jurnal Ilmu Administrasi Publik, 2021)
The village government is at the forefront of implementing public services to ensure the welfare of the community, which is a determining factor for the success of government programs. Increasing the capacity of village officials is an action to create a prosperous society. The village government must make efforts to increase the capacity of its village apparatus considering that the quality of human resources in various villages is generally still low. Therefore, the purpose of this study is to describe the development of the capacity of the apparatus in the dimension of developing the capacity of the human resources of the apparatus. Data collection in this qualitative research was carried out through participant observation, in-depth interviews, and documentation. The informants in this study were the Village Head and the Secretary of Kenongo Village, Tulangan District, Sidoarjo Regency. The data that has been collected will then be analyzed using the interactive analysis model of Miles and Huberman. The results showed that the development of human resource apparatus capacity was carried out through technical guidance from the Village Community Empowerment Service (DPMD), the implementation of technical guidance had not been accompanied by enthusiasm from the Kenongo Village government apparatus. Apparatus capacity development in the IT field has also been carried out, but not accompanied by monitoring and evaluation stages, so that IT training only evaporates without soft skills for Kenongo Village Apparatus. The findings also show that the development of the human resource capacity of village heads also needs to be improved, especially in terms of the ability to communicate with village apparatus staff to create a conducive working climate in government administration. The obstacles in carrying out the development of the capacity of the Village apparatus human resources are the lack of enthusiasm of the village apparatus in following technical guidance, the disinterest / curiosity of the village apparatus in using IT, the existence of passive village officials in planning work programs, and the morale of the apparatus is decreasing, because the salary received is used up for pay bank installments.